Validasi Instrumen Pemahaman Konsep Pada Materi Sel Untuk Siswa SMA - Hajiriah, Titi Laily; Adnyana, Putu Budi; Rapi, Ni Ketut (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to validate concept understanding instruments on cell material for high school students using Content Validity Ratio (CVR) and Content Validity Index (CVI). Instrument validation was conducted by five experts from three different universities. The results showed that most of the items had CVR and CVI values that met the established validity criteria, only a few items were declared invalid and needed to be revised or deleted. Furthermore, the results of the reliability test using Cronbach's Alpha obtained a value of 0.913 which indicates that this instrument has excellent reliability. This valid and reliable instrument can be used by biology teachers in high school to measure students' concept understanding of cell material. The use of this instrument is expected to help identify weak areas of student understanding and design more effective learning strategies. This research supports the importance of instrument validation to ensure the accuracy of measurement results and increase teacher and student confidence in the results obtained. Thus, the instrument that has been developed is expected to contribute significantly to improving the quality of biology learning in high school.